Importance of Telomere Shortening in the Pathogenesis of Ulcerative Colitis: A New Treatment From the Aspect of Telomeres in Intestinal Epithelial Cells. (28th June 2021) - Watanabe, Sho; Hibiya, Shuji; Katsukura, Nobuhiro; Kitagawa, Sayuki; Sato, Ayako; Okamoto, Ryuichi; Watanabe, Mamoru; Tsuchiya, Kiichiro
Abstract: Background and Aims: Ulcerative colitis [UC] is a chronic inflammatory disease of the colon with frequent relapses. Telomere shortening in intestinal epithelial cells has been reported in severe or longstanding cases. However, its influence on UC pathogenesis remains unelucidated. To this end, we evaluated telomere shortening using a long-term organoid inflammation model that we had originally established. Methods: A UC model using human colon organoids was established to assess telomere changes chronologically. MST-312 was used for the telomerase inhibition assay. The potential of telomerase activators as a novel UC treatment was evaluated with an in vitro model, including microarray analysis, and histological changes were assessed using xenotransplantation into mouse colonic mucosa. Results: Our UC model reproduced telomere shortening in vitro, which was induced by the continuous suppression of telomerase activity via P53. MST-312-based analysis revealed that telomere shortening was involved in the pathogenesis of UC. Madecassoside [MD] improved the telomere length of the UC model and UC patient-derived organoids, which further promoted cell proliferation in vitro and improved the graft take-rate of xenotransplantation. Moreover, histological analysis revealed that MD induced normal crypt structure with abundant goblet cells. Conclusions: This study is the first to reveal the mechanism and importance of telomere shortening in the pathogenesis of UC. MD could be a novel candidate for UC treatment beyond endoscopic mucosal healing.